TAXTAKÓPIR RAYONÍ OYKONIMLERINIŃ LEKSIKA-SEMANTIKALÍQ QURAMÍ HÁM ONÍ KARTALASTÍRÍW - Baltabayev, О.О. (SCIENCE and SOCIETY, 2022)
This article has been studied geographically the oikonyms of Takhtakupir district of the Republic of Karakalpakstan. District oikonyms are studied in lexical-semantic groups. A map of Takhtakupir district's oikonyms on lexical-semantic features has been developed.
Keywords: toponym; oikonym; phytooikonym; ethnooikonym; anthropooikonym; hydronym; oronym; oikonymic map